Shared Decision-Making in Emergency Room Setting: A Concept Analysis - Aric Vranada; Jiin-Ru Rong; Satriya Pranata (Universitas Aisyah Pringsewu, 2022)
Shared decision-making” (SDM), a cooperative process that allows health professionals and patients to share the best accessible evidence for making decisions, is extensively accepted and developed in general ward of hospital settings. However, the concept's implementation in an emergency department (ER) setting has not been comprehensively clarified. The objective of this analysis was to describe and elucidate the concept of SDM in the ER setting. The Walker and Avant's concept analysis process was used to analyzing the concept of SDM. Four key defining attributes were identified: “active participation of health professionals and patients or their surrogates; collaborative partnership; reaching a compromise; and common goal for patient's health care”. The antecedent's analysis included “several options with different possible outcomes, substantial decisional conflict, the need to recognize the patient's health situation decision making, and willingness to participate in decision making”. The consequences were identified as “decreased decisional, mutual empowerment, and patient health status improvement”. SDM in the ER setting is a communication process involving health care professionals, patients, and patients' surrogates. The process has the potential to overcome traditional power dynamics and encourage changes that could improve the dyadic relationship.